(untitled) (Faridpur Medical College Journal, 2020)
Dengue fever and dengue hemorrhagic fever emerged as major health problem in South East Asia and Bangladesh as well. The purpose of this study is to determine the use of ultrasound as an important adjunct to clinical and laboratory profile in diagnosing dengue fever and in predicting the severity of the disease. Sixty serologically diagnosed dengue fever patients between August and October 2019 referred for ultrasound scanning of the abdomen and thorax were selected for the study and the findings were analyzed. Out of the 60 patients, 19 (31.67%) had hepatomegaly, thick walled gall bladder, ascites with bilateral pleural effusion; 15 (25%) had hepatomegaly, thick walled gall bladder, ascites and only right sided pleural effusion; 6 (10%) had hepatomegaly and right sided pleural effusion; 5 (8.35%) had hepatomegaly and ascites; 3 (5%) had thick walled gall bladder; 1 (1.66%) patient had left sided pleural effusion and hepatomegaly; 1 (1.66%) patient had only hepatosplenomegaly; 1 (1.66%) had ascites with pericardial effusion and no abnormal sonographic findings was found in 9 individuals (15%). Ultrasound findings should strongly favor the diagnosis of dengue fever in patients presenting with fever and associated symptoms, particularly during an endemic. A simple ultrasound examination will effectively expedite the diagnosis and justifies initiation of specific treatment for dengue fever pending serological confirmation. Ultrasound also helps substantially in estimating the severity of the disease. Faridpur Med. Coll. J. Jul 2019;14(2): 90-92